ANALISIS PENDAPATAN USAHATANI JAGUNG MANIS DI DESA SIDERA KECAMATAN SIGI BIROMARU - Marwah, Marwah; Antara, Made; Howara, Dafina (AGROTEKBIS, 2018)
Sidera Village is a sweet corn producing area in District Sigi Biromaru Sigi Regency. Sweet Corn Farming in Sidera Village is a source of farmers income, which can be seen from the commoditys exploitation. The sustainability of the farm should be maintained to increase the production and income of farmers by maintaining or even increasing the produced production. The purpose of this study was to find out, knowing the amount of sweet corn farm income in Sidera Village Sigi Biromaru District. The study was conducted from October to January. Data analysis used in this research is Production Revenue analysis obtained that Sweet Corn Production in one planting season equal to 1,899.33 / Kg and average of income earned by farmer equal to Rp. 3,273,333./ha, while the total cost incurred by farmers on average amounted to Rp. 1.738.462./ha and Average income of Sweet Corn farming in Sidera Village Sigi Biromaru sub district Sigi Rp. 1.534.870 / ha.Â Keywords : Farming, Sweet Corn, Revenue, Sidera.